Sorghum cultivation under non-traditional areas of eastern Indo-Gangetic plains - Kumar, Rakesh; Prakash, Ved; Hans, Hansraj; Singh, A K; Mishra, J S (Indian Farming, 2022)
Traditionally, sorghum is a staple diet for rural and lower-income, semi-urban households in India. However, with Green Revolution production gains and food security programs subsidized rice and wheat, other coarse grains are being replaced in food baskets. However, there is increased consumption of sorghum among a small population of health conscious, urban consumers seeking to incorporate high-fiber and nutrient rich grains into their diets. Sorghum in eastern India could be grown successfully during summer i.e. second fortnight of February to first week of March. Grain sorghum hybrid CSH 13 (timely sown) gave maximum grain yield, whereas CSH 14 yielded higher when sown on 16 February. Hence, selections of micronutrient enriched genotypes (CSH 16, CSV15, SPV 462) with proper sowing time not only helps in improving nutrient use efficiency, but would also help in addressing the problem of hidden hunger in rural areas